Assessing the satisfaction of teenagers at risk and vulnerable to social damages of young adults' publications in Iran based on the CSI model. (24th September 2018) - Amini, Mahsa; Pashootanizadeh, Mitra
Abstract : Purpose: The purpose of this paper is to assess the satisfaction of teenagers who are suffering from or are exposed to social damages of children and young adults' publications in Iran. Design/methodology/approach: A descriptive surveys approach with practical purposes is applied here. The tools used in this study include two researcher-made questionnaires. Two sets of participants constitute the statistical populations: 120 and 50 teenagers who were affected by or are at the risk of social damages. Data collection from the first set was through census, while the same from the second set is through the disproportionate stratified random sampling method. Another statistical population is the group of premier children publishers during 2006-2016. Findings: The teenagers' satisfaction mainly is involved with: perceived quality, expectations and perceived value. "Music" and "Recreational and performing arts", internet-based resources, "Electronic materials" and "Real stories" are ranked as having the highest mean value in information needs, formats and literacy genre among teenagers, respectively. The findings here indicate that the teenagers participated are satisfied with children publications to a great extent. Originality/value: This is the first research which used the CSI Model for assessing the satisfaction of teenagers at risk and vulnerable to social damages.